2015
DOI: 10.22163/fteval.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation CEEPUS III - Evaluation of CEEPUS’ teacher mobility. Frequent travellers under the microscope

Abstract: AcknowledgmentWe sincerely thank Ms. Elisabeth Sorantin, CEEPUS Secretary General, for her kind cooperation. We are also grateful to all National CEEPUS Offices, teachers, and host organisations who participated in the interviews, discussions and in the online surveys for their valuable inputs.2 CONTENT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Thirdly, they value the development of professional skills and intercultural competences. These results are in line with the international literature of CEEPUS mobility (Javorova 2013;Scheck et al 2015;Welzer et al 2017).…”
Section: The Effects Of Ceepus In Hungarysupporting
confidence: 91%
See 1 more Smart Citation
“…Thirdly, they value the development of professional skills and intercultural competences. These results are in line with the international literature of CEEPUS mobility (Javorova 2013;Scheck et al 2015;Welzer et al 2017).…”
Section: The Effects Of Ceepus In Hungarysupporting
confidence: 91%
“…Highlight and communicate the outstanding multilateral cooperation opportunities and relatively easy availability of non-EU state partnerships and mobilities. It is in line with the suggestions of the international impact study conducted by Scheck et al (2015).…”
Section: Recommendationssupporting
confidence: 90%
“…Thus, the official program objectives do not mention culture. The research conducted among the academic teachers who have participated in the project indicate the following motives to participate: teach lectures (68%); build up sustainable professional contacts (62%); get an experience abroad in general (58%); interest in a particular teaching domain of the partner institution (54%); friendship (53 %); participation in a CEEPUS network (53%); interest in internationalization (Scheck, Zupan, Schuch, 2015). As revealed, the above mentioned goals do not refer to intercultural issues.…”
Section: Analysis Of Selected International Exchange Programsmentioning
confidence: 99%
“…CEEPUS networks have delivered an impressive number of scientific papers and by focusing on PhD students are training the future scientific elite of the region -and the fact that they are regional networks with many destinations makes for brain circulation rather than brain drain. A follow up study on the last overall evaluation (Scheck & Manahl, 2015) has shown that CEEPUS has become an important regional career factor, documenting career paths starting as a CEEPUS exchange student and then using CEEPUS contacts to successfully promote one´s career, even ending up as head of a department (Scheck & Manahl, 2016, p. 12).…”
Section: The Ceepus Experiencementioning
confidence: 99%